GEBELİĞİN 20. HAFTASINDA UTERİN ARTER DOPPLERİ VE MATERNAL SERUM ALFA-FETOPROTEİN İLİŞKİSİ - ULUDAĞ, Seyfettin; MADAZLI, Rıza; OCAK, Vildan; DİRİCAN, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background.- In this study, we obtained uterine artery Doppler at 20th week of gestation for prediction of preeclampsia, intrauterine growth retardation (IUGR) and preterm labor. We determined the relationship of early diastolic notch and abnormal uterine artery Doppler with maternal serum afetoprotein (MSAFP) levels for prediction of adverse pregnancy outcome. Design.- In a group of high risk, except fetal anomaly, multiple pregnancy and type 1 DM, 80 pregnant women were followed as a study group prospectively. MSAFP levels at the 15-17th weeks of gestation and bilateral uterine artery Doppler at the 20th week.s of gestation were obtained. Results.- Uterine artery early diastolic notch were determined at 20th weeks of gestation in 17 (21,75 %) cases. Early diastolic notch in Doppler was persistent at the 24th weeks in the nine of cases, and in the eight of cases, it was disappeared. In uterine artery Doppler, diastolic notch was found to be a significant predictive factor for preeclampsia, IUGR and preterm labor (p<0.001, OR: 69.74; p<0.02, OR: 10.11; p<0.05, OR: 3,75 respectively). MSAFP levels of 17 cases that displayed early diastolic notch in uterine artery Doppler were significantly higher than the notch negative cases (p<0.05). The levels of MSAFP, in 9 cases which demonstrated the persistence of diastolic notch, were significantly higher then in 8 cases that the notch was disappeared, at 24th week of gestation (p<0.05). MSAFP levels were found to be significantly elevated in the pregnant with preeclampsia; IUGR and preterm labor then the cases that have not any of these complications. Conclusion.- Our findings suggested that the abnormal uterine artery Doppler was together with elevated MSAFP levels at 20 th week of gestation. Bilateral diastolic notch in uterine artery Doppler and elevated levels of MSAFP at the 20th week.s of gestation will be more sensitive for prediction of adverse obstetric outcomes.